PENGARUH DISCRETIONARY ACCRUALS, BEBAN PAJAK TANGGUHAN DAN BEBAN PAJAK KINI TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PERTAMBANGAN DAN ENERGI DI BURSA EFEK INDONESIA TAHUN 2012 – 2016 - Lucky Lukman; Miyv Fayzhall (LPPM Sekolah Tinggi Ilmu Ekonomi Cirebon, 2019)
ABSTRACTThe purpose of this study was to analyze and examine the effect of discretionary accrued, deferred tax expenses and current tax expenditures on the profit management in mining and energy companies in the Indonesian Stock Exchange. The method used is explanatory research (explanatory research) to explain the causal relationships between the variables examined in a model, through test hypotheses. The analysis technique used is the multiple regression analysis and cross section and panel data. The results of the research show that, simultaneously, discretionary accrued, deferred tax expenses and current tax expenditures have a significant effect on profit management. Discretionary accrued, deferred tax expenses and current tax expenses partially have a negative and significant effect on profit management.ABSTRACTThe purpose of this study was to analyze and examine the effect of discretionary accrued, deferred tax expenses and current tax expenditures on the profit management in mining and energy companies in the Indonesian Stock Exchange. The method used is explanatory research (explanatory research) to explain the causal relationships between the variables examined in a model, through test hypotheses. The analysis technique used is the multiple regression analysis and cross section and panel data. The results of the research show that, simultaneously, discretionary accrued, deferred tax expenses and current tax expenditures have a significant effect on profit management. Discretionary accrued, deferred tax expenses and current tax expenses partially have a negative and significant effect on profit management.